The practicality of problem-based learning tools assisted by interactive simulations to improve students' creative thinking ability - Ratnah Ratnah; Wildan Wildan; Muntari Muntari (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
Learning tools are important to facilitate students in improving creative thinking skills. The ultimate goal of this research is to produce practical problem-based learning tools assisted by interactive simulations. This research uses a 4D development model: define, design, develop, and disseminate. The interactive simulation-assisted problem-based learning tool that was developed consisted of a syllabus, lesson plans, worksheets, and evaluation instruments. The research subjects used were students of class XI MA in Mataram City. The practicality test is carried out by observing the implementation of learning, the process of creative thinking skills during learning, and teacher and student responses related to learning and learning tools. The results of the practicality test showed in the practical category. They received a positive response from both teachers and students, with the percentage range of the practicality of all indicators being 60% to 80%.